MULTI-STOREY HYBRID BUILDINGSUSING TIMBER-STEEL - Siddesh R.Sable; Mr. Shankar Banerjee (International Journal of Innovations in Engineering Research and Technology, 2021)
Timber construction is mostly used and bestsuited for multi storey buildings as it has very high strength to weight ratio. Timber construction is well suited for earth quake prone areas as timber is light in weight. Timber construction also has an advantage of reduced load on foundation as compared to traditional reinforced concrete building. The timber construction can be used for both residential as well as commercial. Properly designed timber buildings can have large number of rooms on each floor also it can sustain permanent load because of permanent wall. Timber construction is widely used in Europe and Turkey as it has light framing. To increase the lateral load resistance, more number of wallsisbuilt. But inpractice timber multi storey buildings has an possesses an open spaces and very few walls. Timber columns and beams has an limitation that they are visible from outside. In this paper more focus is given on the energy consumption and global warming potential of various building is also been briefed.